Highly reactive light‐dependent monoterpenes in the Amazon. Issue 5 (6th March 2015) - Jardine, A. B.; Jardine, K. J.; Fuentes, J. D.; Martin, S. T.; Martins, G.; Durgante, F.; Carneiro, V.; Higuchi, N.; Manzi, A. O.; Chambers, J. Q.
Abstract: Despite orders of magnitude difference in atmospheric reactivity and great diversity in biological functioning, little is known about monoterpene speciation in tropical forests. Here we report vertically resolved ambient air mixing ratios for 12 monoterpenes in a central Amazon rainforest including observations of the highly reactive cis‐ β ‐ocimene (160 ppt), trans‐ β ‐ocimene (79 ppt), and terpinolene (32 ppt) which accounted for an estimated 21% of total monoterpene composition yet 55% of the upper canopy monoterpene ozonolysis rate. All 12 monoterpenes showed a mixing ratio peak in the upper canopy, with three demonstrating subcanopy peaks in 7 of 11 profiles. Leaf level emissions of highly reactive monoterpenes accounted for up to 1.9% of photosynthesis confirming light‐dependent emissions across several Amazon tree genera. These results suggest that highly reactive monoterpenes play important antioxidant roles during photosynthesis in plants and serve as near‐canopy sources of secondary organic aerosol precursors through atmospheric photooxidation via ozonolysis. Key Points: Mixing ratios of 12 Amazon monoterpenes reflect vertical forest structure Light‐dependent reactive monoterpene leaf emissions observed in ambient air Monoterpene ozonolysis rates suggest important local aerosol precursor source